2011
DOI: 10.1590/s0037-86822011000500001
|View full text |Cite
|
Sign up to set email alerts
|

Mother-to-child transmission of HIV infection in Manaus, State of Amazonas, Brazil

Abstract: INTRODUCTION: Reduction in the vertical transmission of HIV is possible when prophylactic measures are implemented. Our objective was to determine demographic characteristics of HIV-infected pregnant women and the rate of mother-to-child transmission of HIV in Manaus, Amazonas, Brazil. METHODS: A descriptive study was conducted using notification, and investigating data from the Notifiable Diseases Data System in the Brazilian State of Amazonas, between 2007 and 2009. RESULTS: During the study period, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 18 publications
2
13
0
4
Order By: Relevance
“…This proportion was higher than that observed in the Sentinel Parturient Study of 2006 [4], when 62.8% of the pregnant women analyzed presented with an HIV serological test. Our results thus corroborate the findings from recent local studies [13,18,19,23,24], which indicated coverage close to 80%. Although a notable increase in this coverage was seen, regional differences were still observed.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This proportion was higher than that observed in the Sentinel Parturient Study of 2006 [4], when 62.8% of the pregnant women analyzed presented with an HIV serological test. Our results thus corroborate the findings from recent local studies [13,18,19,23,24], which indicated coverage close to 80%. Although a notable increase in this coverage was seen, regional differences were still observed.…”
Section: Discussionsupporting
confidence: 92%
“…The decline in mortality due to AIDS in Brazil since the 2000s [3], with increasing survival among HIV-infected individuals [46,47], is one possible explanation. The high proportion of pregnant women with diagnoses of HIV infection prior to the current pregnancy, which has been reported in several national studies [11,13,14,18,19], suggests that women who have been infected for longer periods are becoming pregnant, which may also explain the increase in prevalence with age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies conducted in Brazil assessing the frequency of MTCT differed in the rates of infection in children, with the incidence ranging from 2.8 to 9.9% [8][9][10][11][12][13] . Despite the free access to ART in Brazil, MTCT is not under control.…”
mentioning
confidence: 99%